SISTEM PENDIDIKAN DI NEGARA AMERIKA SERIKAT - Abdul Wahab Syakhrani; Al Hidayatullah, M. Azhar, Muhammad Zulkifli, Fajar Asshadiqi (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2022)
The United States of America which is the third largest country in the world certainly has a quality education system, many of the American universities are able to provide quality human resources in the world of work and education. in carrying out the educational process, as with the United States which gives more freedom to the states to implement the education system, while the central government only formulates big things in education. Basic education in the three countries has differences in the minimum age limit for entering primary school. In addition, the order of the education systems of the three countries is also different, as well as the level and type of education. As for the curriculum, in Indonesia the curriculum is described in a centralized curriculum structure, and basic education is given 10 subjects but has not been added with local content. In Japan, the basic education curriculum is based on cultivating character and independence, while general science lessons are only 4 subjects. Meanwhile, in the United States, the basic education curriculum teaches more soft skills and general subjects, totaling 4 subjects and then lowering them into sharpening sub-subjects.